A new mouse model of post-traumatic joint injury allows to identify the contribution of Gli1+ mesenchymal progenitors in arthrofibrosis and acquired heterotopic endochondral ossification - Magallanes, Jenny; Liu, Nancy Q.; Zhang, Jiankang; Ouyang, Yuxin; Mkaratigwa, Tadiwanashe; Bian, Fangzhou; Van Handel, Ben; Skorka, Tautis; Petrigliano, Frank A.; Evseenko, Denis (Frontiers in Cell and Developmental Biology, 2022)
Complex injury and open reconstructive surgeries of the knee often lead to joint dysfunction that may alter the normal biomechanics of the joint. Two major complications that often arise are excessive deposition of fibrotic tissue and acquired heterotopic endochondral ossification. Knee arthrofibrosis is a fibrotic joint disorder where aberrant buildup of scar tissue and adhesions develop around the joint. Heterotopic ossification is ectopic bone formation around the periarticular tissues. Even though arthrofibrosis and heterotopic ossification pose an immense clinical problem, limited studies focus on their cellular and molecular mechanisms. Effective cell-targeted therapeutics are needed, but the cellular origin of both knee disorders remains elusive. Moreover, all the current animal models of knee arthrofibrosis and stiffness are developed in rats and rabbits, limiting genetic experiments that would allow us to explore the contribution of specific cellular targets to these knee pathologies. Here, we present a novel mouse model where surgically induced injury and hyperextension of the knee lead to excessive deposition of disorganized collagen in the meniscus, synovium, and joint capsule in addition to formation of extra-skeletal bone in muscle and soft tissues within the joint capsule. As a functional outcome, arthrofibrosis and acquired heterotopic endochondral ossification coupled with a significant increase in total joint stiffness were observed. By employing this injury model and genetic lineage tracing, we also demonstrate that Gli1+ mesenchymal progenitors proliferate after joint injury and contribute to the pool of fibrotic cells in the synovium and ectopic osteoblasts within the joint capsule. These findings demonstrate that Gli1+ cells are a major cellular contributor to knee arthrofibrosis and acquired heterotopic ossification that manifest after knee injury. Our data demonstrate that genetic manipulation of Gli1+ cells in mice may offer a platform for identification of novel therapeutic targets to prevent knee joint dysfunction after chronic injury.